THE APPLICATION OF SOCIAL IMPACT ASSESSMENT IN NEW AIRPORT DEVELOPMENT PROJECT IN KULONPROGO – YOGYAKARTA, INDONESIA - Putro, Heru Purboyo; Kusumawati, Dedes (PEOPLE: International Journal of Social Sciences, 2015)
Airport as a crucial infrastructure will give a lot of benefits such as economic growth. Nevertheless, its development often neglects social impacts which can be negative impacts for some stakeholders. The purpose of this paper is to suggest the potential application of social impact assessment in a new airport project. It uses a case study, a new airport development project in Yogyakarta, Indonesia, for its methodology to understand the social phenomena regarding to the facts, conditions and phenomena occurred, especially the impacts for local communities. To apply the social impact assessment, this study identifies the related stakeholders and the impacts which can be possibly affected toward them. After that, the study develops mitigation strategies to minimize the negative impacts, and also maximizing the positive impacts for all stakeholders. Then, the study suggests a monitoring program in order to get the effectively of the project. This study concludes that the application of SIA is essentially needed for achieving success in a project management.